Is Reduced Visitation a Collateral Consequence of Restrictive Housing? - Anderson, Claudia N. (Criminal justice and behavior, 2022)
Theory and logic suggest that placement in restrictive housing (RH) may affect prison visitation, which may be counterproductive given the potential benefits of visitation. The goal of this paper is to examine the potential correspondence between RH and visitation. We use data on incarcerated people in Ohio to conduct two related analyses. One analysis assesses whether the first incident of short-term disciplinary segregation impacts prison visits shortly after segregation. The second analysis examines longitudinal patterns of RH stays and visits to understand the interplay of the two throughout a prison term. Findings suggest that disciplinary segregation might reduce the odds of visitation immediately. RH early in a prison term may also operate to “cut off” future visitation. These results highlight an important knowledge gap and suggest that more research is needed that disentangles how RH may lead to the dissolution of social ties. Implications for research are discussed.